Antihypertensive Drug Use and COVID‐19 Disease Severity in Hospitalized US Veterans: A Retrospective Cohort Study - Merodean Huntsman; Jessica L. Marquez; Gregory J. Stoddard; Guo Wei; Aaron J. Miller; Jayant P. Agarwal; Sujee Jeyapalina (The Journal of Clinical Hypertension)
ABSTRACT This research investigated associations between hypertensive patients with COVID‐19 who did and did not use specific antihypertensive medications and had incurred hospital ventilation/death in the US Veterans Hospital System. This study included de‐identified medical records of 572 994 hypertensive US veterans who were diagnosed with COVID‐19 and hospitalized between March 1, 2020, and February 28, 2022, with a 60‐day follow‐up period. Mechanical ventilation and/or death within 60 days of COVID‐19 hospitalization served as the outcome variables. On multivariable analysis, CCB use was associated with a 9% increased risk of mechanical ventilation, while ACE inhibitors (HR: 0.90), alpha blockers (HR: 0.92), and CCB (HR: 0.93) users were associated with a significantly decreased risk of death. Additional multivariable analysis on those with and without additional comorbidities, such as chronic kidney disease (CKD), heart failure, and diabetes, revealed that in those with at least one additional comorbidity, CCB uses led to a 9% increased deleterious risk for ventilation. In contrast, the use of ACE inhibitors (HR: 0.86), alpha blockers (HR: 0.92), and CCB (HR: 0.93) demonstrated a moderate protective effect against mortality. Lastly, in hypertensive veterans without any additional comorbidities, there was a lack of significant association between hypertensive medication usage and mechanical ventilation and/or death. In summary, although CCB use was associated with an increased risk of requiring mechanical ventilation, it also demonstrated a protective effect against mortality. At the same time, ACEI, alpha blocker, and CCB usage led to a significantly decreased risk for death within all hypertensive hospitalized COVID‐19 veteran cohorts.